Flow Cytometric Bivariate Analysis of DNA and Cytokeratin in Colorectal Cancer - Carolin Post; Ib Jarle Christensen; Henrik Flyger; Jette Christiansen; Jørgen K. Larsen (Analytical Cellular Pathology)
Different opinions about flow cytometric estimates of DNA aneuploidy and/or S‐phase fraction (SPF) as supplementary prognostic markers in colorectal cancer are to some degree associated with methodology. Using univariate DNA analysis, we have previously investigated the DNA ploidy in colorectal cancer, its heterogeneity within and between tumors and its relation to survival. To improve detection of DNA aneuploid subpopulations and particularly estimation of their SPF's we investigated a method for bivariate DNA/cytokeratin analysis on fine‐needle aspirates of 728 frozen biopsies from 157 colorectal tumors. Unfixed aspirates were stained with propidium iodide and FITC‐conjugated anti‐cytokeratin antibody in a saponin‐buffer. A significant association between SPF and debris was observed. There were no substantial difference in DNA ploidy patterns between univariate and bivariate measurements (concordance was 92–95%). No new DNA aneuploid subpopulations were detected in cytokeratin‐gated compared to ungated or univariate histograms. Debris‐adjusted SPF's of cytokeratin‐gated histograms were significantly higher than of ungated histograms, also for subpopulations with DI>1.4 (p < 0.0001). There was no significant association between SPF and survival.